Primary duodenal tuberculosis complicated with perforation: A review of literature and case report. (June 2021) - Souhaib, Atri; Magherbi, Houcine; Yacine, Ouadi; Hadad, Anis; Alia, Zehani; Chaker, Youssef; Kacem, Montasser Jamel
Abstract: Tuberculous (TB) disease remains an endemic pathology in Tunisia. the ileocecal region is the predominant site of involvement while gastroduodenal tuberculosis is very rare, this form is often presenting as one of the complications, mainly upper gastrointestinal stenosis or exceptionally as a perforation. We describe a case of female patient aged 33 years-old presented with a 2-day history of acute abdominal pain, with a tenderness of the right hypochondrium and the epigastrium, ultrasound of the abdomen revealed gallbladder distension with a wall thickening. The diagnosis of acute cholecystitis was suspected and the patient had an exploratory laparoscopy that revealed the presence of a perforated duodenal ulcer which was blocked by the gallbladder and several peri-duodenal lymph nodes. Cholecystectomy was performed and the edges of the ulcer were resected and the ulcer was sutured. Histological examination revealed duodenal tuberculosis and the patient was referred to the TB eradication program. Highlights: The primary duodenal tuberculosis is very rare. The perforation is an exceptional complication its described for the second time in literature. The diagnosis is difficult with no clinical and endoscopic features. Surgical approach is recommended in complicated forms with antituberculos treatment.